Staging the Sounds of the Nation: The Poetic Soundscapes of the USA - Fernández-Caparrós, Ana; Hernando Real, Noelia; L. Vericat, Fabio (Complutense Journal of English Studies, 2015)
Staging the Sounds of the Nation: The Poetic Soundscapes of the USA